Pharmacotherapy Update and Review for Family Medicine Residents Using Jeopardy-Style Game - Giselle Ellis (Association of American Medical Colleges, 2020)
Introduction Pharmacotherapy is an important, required aspect of family medicine residency training. MedEdPORTAL has very limited pharmacotherapy content that is targeted to a graduate medical education audience. Methods I implemented a Jeopardy-style game during a 1-hour didactic session to actively engage the family medicine residents. The game focused on reinforcing guidelines and teaching new medications. I created a session-specific evaluation tool to assess the residents' enjoyment of and learning from the activity. Results Twenty-six family medicine residents participated in the session, working in groups of three or four. I evaluated the session using the session-specific evaluation tool and a standard didactics evaluation. Twenty-three of 26 residents completed the session-specific evaluation; all 26 completed the standard evaluation. All the residents agreed or strongly agreed that the session was enjoyable, an opportunity for learning, and something they would look forward to in the future. All the residents also agreed that the information presented applied to clinical practice. Comments primarily focused on the difficulty of the questions and the enjoyment of the session. Discussion Based upon the results of the evaluations and comments, the residents felt the session was a valuable opportunity for learning. The session could be easily implemented by other family medicine or internal medicine programs. The tool can and should be updated as required to remain accurate and current.